Thermoluminescence and fluorescence study of changes in Photosystem II photochemistry in desiccating barley leaves - Skotnica, J; Matousková, M; Naus, J; Lazár, D; Dvorák, L (Photosynthesis research, 2000)
An effect of desiccation (a decrease of relative water content from 97% to 10% within 35 h) on Photosystem II was studied in barley leaf segments (Hordeum vulgare L. cv. Akcent) using chlorophyll a fluorescence and thermoluminescence (TL). The O-J-I-P fluorescence induction curve revealed a decrease of F(P) and a slight shift of the J step to a shorter time with no change in its height. The analysis of the fluorescence decline after a saturating light flash revealed an increased portion of slow exponential components with increasing desiccation. The TL bands obtained after excitation by continuous light were situated at about -27 degrees C (Z(v) band - recombination of P680(+)Q(A) (-)), -14 degrees C (A band - S(3)Q(A) (-)), +12 degrees C (B band - S(2/3)Q(B) (-)) and +45 degrees C (C band - TyrD(+)Q(A) (-)). The bands related to the S-states of oxygen evolving complex (A and B) were reduced by desiccation and shifted to higher and lower temperatures, respectively. In accordance with this, the band observed at about +27 degrees C (S(2)Q(B) (-)) after excitation by 1 flash fired at -10 degrees C and band at about +20 degrees C (S(2/3)Q(B) (-)) after 2 flashes decreased with increasing water deficit and shifted to lower temperatures. A new band around 5 degrees C appeared in both regimes of TL excitation for a relative water content of under 42% and was attributed to the Q band (S(2)Q(A) (-)). It is suggested that under desiccation, an inhibition of the formation of S(2)- and S(3)-states in OEC occurred simultaneously with a lowering of electron transport on the acceptor side of PS II. The temperature down-shift of the TL bands obtained after the flash excitation was induced at the initial phases of water stress, indicating a decrease of the activation energy for the S(2/3)Q(B) (-)recombination.